Phacoemulsification combined with goniosynechialysis versus phacoemulsification alone for patients with primary angle‑closure disease: A meta-analysis. - Lin Yao; Haitao Wang; Yunxiao Wang; Pengpeng Zhao; Haiqing Bai (PLoS ONE, 2024)
This meta-analysis aims to systematically compare the efficacy between phacoemulsification (PE) combined with goniosynechialysis (GSL) and PE alone for primary angle-closure disease (PACD) patients. All the data were searched from the PubMed, EMBASE and the Cochrane Library. The Cochrane Handbook was used to evaluate the quality of the included studies. Additionally, this meta-analysis was performed by using the Revman 5.4 software. Nine randomized controlled trials (RCTs) were included in this study. Compared with PE alone group, PE+GSL could result significant reduction in the IOP (MD, 1.81; p = 0.002). In the instrumental subgroup, also more reduction of IOP was shown in the PE+GSL group (MD, 2.11; p = 0.02). In the viscogonioplasty (VGP) subgroup, there was not no statistical difference between PE alone group and PE+GSL group (MD, 1.53; p = 0.11). Also, more reduction of peripheral anterior synechiae (PAS) was shown in the PE+GSL group (MD,59.15; p<0.00001). For the change in angle open distance (AOD)500, AOD 750, trabecular-iris space (TISA)500, number of glaucoma medications and best corrected visual acuity (BCVA), there was no difference between two groups (p = 0.25, 0.35, 0.17, 0.56, 0.08). For TISA 750, more improvement was shown in the PE+GSL group (p<0.00001). Instrumental separation had better effect on lowering IOP when it combined with PE. Both instrumental separation and VGP could reduce postoperative PAS. The operation of GSL has no obvious effect on postoperative vision.